Safety and immunogenicity of INO-4800 DNA vaccine against SARS-CoV-2: A preliminary report of an open-label, Phase 1 clinical trial. (January 2021) - Tebas, Pablo; Yang, ShuPing; Boyer, Jean D.; Reuschel, Emma L.; Patel, Ami; Christensen-Quick, Aaron; Andrade, Viviane M.; Morrow, Matthew P.; Kraynyak, Kimberly; Agnes, Joseph; Purwar, Mansi; Sylvester, Albert; et al.
Abstract: Background: A vaccine against SARS-CoV-2 is of high urgency. Here the safety and immunogenicity induced by a DNA vaccine (INO-4800) targeting the full length spike antigen of SARS-CoV-2 are described. Methods: INO-4800 was evaluated in two groups of 20 participants, receiving either 1.0 mg or 2.0 mg of vaccine intradermally followed by CELLECTRA® EP at 0 and 4 weeks. Thirty-nine subjects completed both doses; one subject in the 2.0 mg group discontinued trial participation prior to receiving the second dose. ClinicalTrials.gov identifier: NCT04336410. Findings: The median age was 34.5, 55% (22/40) were men and 82.5% (33/40) white. Through week 8, only 6 related Grade 1 adverse events in 5 subjects were observed. None of these increased in frequency with the second administration. No serious adverse events were reported. All 38 subjects evaluable for immunogenicity had cellular and/or humoral immune responses following the second dose of INO-4800. By week 6, 95% (36/38) of the participants seroconverted based on their responses by generating binding (ELISA) and/or neutralizing antibodies (PRNT IC50 ), with responder geometric mean binding antibody titers of 655.5 [95% CI (255.6, 1681.0)] and 994.2 [95% CI (395.3, 2500.3)] in the 1.0 mg and 2.0 mg groups, respectively. For neutralizing antibody, 78% (14/18) and 84% (16/19) generated a response with corresponding geometric mean titers of 102.3 [95% CI (37.4, 280.3)] and 63.5 [95% CI (39.6, 101.8)], in the respective groups. By week 8, 74% (14/19) and 100% (19/19) of subjects generated T cell responses by IFN-ɣ ELISpot assay with the median SFU per 10 6 PBMC of 46 [95% CI (21.1, 142.2)] and 71 [95% CI (32.2, 194.4)] in the 1.0 mg and 2.0 mg groups, respectively. Flow cytometry demonstrated a T cell response, dominated by CD8 + T cells co-producing IFN-ɣ and TNF-α, without increase in IL-4. Interpretation: INO-4800 demonstrated excellent safety and tolerability and was immunogenic in 100% (38/38) of the vaccinated subjects by eliciting either or both humoral or cellular immune responses. Funding: Coalition for Epidemic Preparedness Innovations (CEPI).